Subdialect Classification of Manggarai Language Using Dialectometry Calculation and Gabmap - Salahuddin (Linguistik Indonesia, 2025)
Verheijen (1967) noted that there are 43 sub-dialects of the Manggarai language, which are grouped into five dialect groups: West Manggarai, West-Central Manggarai, Central Manggarai, East Manggarai, and Far East Manggarai. However, the Language Development and Fostering Agency states that the Manggarai language has five dialects, including the Tangge dialect in West Manggarai Regency. Neither study was accompanied by scientific evidence underlying the sub-dialect grouping. Therefore, this research aims to provide quantitative evidence to re-evaluate the variations of the Manggarai language, especially those spoken in West Manggarai Regency. Data was obtained by asking 200 Swadesh vocabularies in ten sample observation areas. The results show that the Manggarai language in West Manggarai Regency is divided into three sub-dialect variations, namely the Kempo sub-dialect (MSdK), the Kolang sub-dialect (MSdS>H), and the Transition area sub-dialect (MSdT). Consistent grouping based on dialectometric calculations and cluster analysis proves that MSdK includes Mbuit, Watu Wangka, Sano Nggoang, Siru, and Benteng Dewa. On the other hand, MSdS>H only consists of Golo Lajang Barat because it shows high linguistic differences from other nearby areas. The MSdT includes Watu Waja, Poco Rutang, Lale, and Tentang. Still, the inclusion of Watu Waja in this group needs to be reconsidered because of the differences in results between dialectometric calculations and cluster analysis.